Voluntary disclosure with multiple channels and investor sophistication - CROWLEY, Richard M. (Institutional Knowledge at Singapore Management University, 2018)
An analytical model of voluntary disclosure in which a manager can disclose through two channels with different ease of processing, and with two types of investors. The model shows that in the presence of a second channel, managers have an incentive to decrease disclosures that will be quickly processed by unsophisticated investors and to increase the disclosures that will be quickly processed by sophisticated investors. The model has implications for post Reg-FD market efficiency, as well as the efficiency of firms having multiple disclosure venues.